الإسعافات النفسية الأولية أثناء الكوارث الطبيعية والأوبئة - خشخوش, صالح (جامعة الوادي - University of Eloued, 2022)
يسلط هذا المقال الضوء على التدخل في الأزمات والكوارث ويتعلق الأمر بالإسعاف النفسي الأولي، من خلال هذا المقال سيعرض الباحث أهم خطوات الاسعاف الاولي وشروط الأساسية . في الجزء الثاني من المقال سيتم عرض تجارب عيادية للتدخل في الأزمات وهنا نقصد فترة الحجر الصحي والحرائق التي عرفتها الجزائر، خلال عرض الوضعيات العيادية سيتم مقارنة بين التدخل عن بعد خلال فترة الحجر الصحي، والتدخل الميداني خلال الحرائق من حيث الخطوات و المنهجية المتبعة. This article sheds light on the intervention in crisis and disasters, and it is related to psychological first aid. Through this article, the researcher presents the most important steps of first aid and the basic conditions. In the second part of the article, clinical experiences of crisis intervention are presented. Here, we mean the period of quarantine and fires that Algeria has known. During the presentation of clinical situations, a comparison is made between remote intervention during the quarantine period and field intervention during fires in terms of the steps and methodology followed.
Psychological First Aid During Natural Disasters and Epidemics
مقال
Keywords: الصدمة النفسية ، الاسعاف النفسي; coronavirus, psychological first aid, psychological trauma.